2015
DOI: 10.1590/s1984-29612015051
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium spp. and Giardia spp. in a public water-treatment system, Paraná, Southern Brazil

Abstract: The purpose of this study was to investigate the occurrence of Cryptosporidium spp. and Giardia spp. in a public water-treatment system. Samples of raw and treated water were collected and concentrated using the membrane filtration technique. Direct Immunofluorescence Test was performed on the samples. DNA extraction using a commercial kit was performed and the DNA extracted was submitted to a nested-PCR reaction (n-PCR) and sequencing. In the immunofluorescence, 2/24 (8.33%) samples of raw water were positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
(39 reference statements)
0
13
0
3
Order By: Relevance
“…The presence of C. hominis in raw sewage samples indicates the occurrence of cryptosporidiosis in humans in the study area. The presence of C. parvum in sewage specimens may suggest the occurrence of an urban zoonotic cycle in this geographic region as this species has also been found in our area in raw water (ALMEIDA et al, 2015). Nevertheless, since C. parvum infects a wide range of hosts, we were unable to determine if the oocysts were of human or animal origin.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The presence of C. hominis in raw sewage samples indicates the occurrence of cryptosporidiosis in humans in the study area. The presence of C. parvum in sewage specimens may suggest the occurrence of an urban zoonotic cycle in this geographic region as this species has also been found in our area in raw water (ALMEIDA et al, 2015). Nevertheless, since C. parvum infects a wide range of hosts, we were unable to determine if the oocysts were of human or animal origin.…”
Section: Discussionmentioning
confidence: 81%
“…In Brazil, these organisms have been found in a variety of samples from different sources including raw water, spring water, bottled water, treated sewage, raw sewage, sewage sludge, and vegetables (ALMEIDA et al, 2015;BONATTI & FRANCO, 2016;BRANCO et al, 2012;FRANCO & CANTUSIO, 2002;SANTOS et al, 2011;TIYO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…in recreational waters, but many studies have identified oocysts of the parasite in water sources used for human consumption (ARAÚJO et al, 2011;BASTOS et al, 2004;CARDOSO et al, 2003;CORTES et al, 2014;SANTOS et al, 2004). Almeida et al (2015) analyzed samples of untreated water and found 8.33% positive samples for Cryptosporidium sp. in the city of Londrina, Paraná.…”
Section: Introductionmentioning
confidence: 99%
“…Em 2001, oocistos de Cryptosporidium spp. foram encontrados em fezes de indivíduos com diarreia no Hospital das Clínicas da cidade de São Paulo (Gonçalves et al, 2006 Almeida et al (2015) encontraram cistos de Cryptosporidium spp e oocistos de Giardia spp. em amostras de água antes e depois do tratamento em uma ETA de ciclo completo.…”
Section: Protozoários Em áGuas De Abastecimentounclassified